Urgency of Notification to the Owners of Collateral Goods in the Sale of Receivables Accompanied by Credit Transfer by Cession - wijaya, Sevi Puri; Djumikasih; Susilo, Hariyanto (Rescollacom (Research Collaborations Community), 2025)
Banking plays a vital role in society, especially with increasingly accessible credit facilities. Loans or credit must include collateral in the form of a mortgage, which must be fully surrendered to the creditor. However, a common problem in credit provision is bad debt or the inability of the debtor to fulfill their obligations. One solution adopted by the bank is the transfer of receivables (cession). In the transfer of receivables, several obligations must be fulfilled by the creditor, namely notification and the preparation of a deed of cession to the debtor and the collateral owner regarding the transfer of rights, as stipulated in the Civil Code. The purpose of this study is to analyze the meaning of notification to the collateral owner and the debtor, or approval in the sale of receivables accompanied by the transfer of credit through cession, and to analyze the legal protection for the collateral owner or the sale of receivables accompanied by the transfer of credit. This legal research is a normative legal research, the types and sources of data used are primary data, namely statutory provisions, and secondary legal materials, namely books, journals, and interviews collected by the author. Notification and approval of the collateral owner is the most important factor in the transfer of a cession and if it is not implemented, it will make the cession have no legal impact on the debtor or even be null and void by law.